#13 Measure your Calibre

Calculus Level 4

lim x 0 cos x cos x 3 sin 2 x = A B \large \lim_{x \to 0} \frac{\sqrt{\cos x} - \sqrt[3]{\cos x}}{\sin^2x} = \frac{A}{B}

The limit above holds true for coprime integers A A and B B , where A A is negative and B B is positive. Find A + B A+B .

Bonus : Evaluate this limit without applying L'Hôpital's rule .


Other problems: Check your Calibre


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sabhrant Sachan
Mar 10, 2017

L = lim x 0 ( cos x ) 1 2 ( cos x ) 1 3 sin 2 x = lim x 0 ( cos x ) 1 2 ( cos x ) 1 3 1 cos 2 x = 1 2 lim x 0 ( cos x ) 1 2 ( cos x ) 1 3 1 cos x Take cos x = t 6 = 1 2 lim t 1 t 3 t 2 1 t 6 = 1 2 lim t 1 t 2 ( t 1 ) ( t + 1 ) ( t 1 ) ( t 4 + t 2 + 1 ) \begin{aligned} L & = \displaystyle\lim_{x \to 0 } \dfrac{(\cos{x})^{\frac12}-(\cos{x})^{\frac13}}{\sin^{2}{x}} \\ & = \displaystyle\lim_{x \to 0 } \dfrac{(\cos{x})^{\frac12}-(\cos{x})^{\frac13}}{1-\cos^{2}{x}} \\ & =\dfrac{1}{2} \displaystyle\lim_{x \to 0 } \dfrac{(\cos{x})^{\frac12}-(\cos{x})^{\frac13}}{1-\cos{x}} \hspace{8mm} \small\text{Take } \cos{x} = t^{6} \\ & = \dfrac{1}{2}\displaystyle\lim_{t \to 1 } \dfrac{t^3-t^2}{1-t^6} \\ & = -\dfrac{1}{2}\displaystyle\lim_{t \to 1 } \dfrac{t^2(t-1)}{(t+1)(t-1)(t^4+t^2+1)} \end{aligned}

L = 1 12 \boxed{ L = -\dfrac{1}{12} }

How did you get rid of the 1+cosx and where did the 1/2 come from on the 3rd step?

Ashish Sacheti - 4 years, 2 months ago

Log in to reply

Using the property of limits

lim x a [ f ( x ) g ( x ) ] = lim x a f ( x ) lim x a g ( x ) \displaystyle \lim_{x \to a} \left[ f(x) \cdot g(x) \right] = \lim_{x \to a} f(x) \cdot \lim_{x \to a} g(x)

We can simplify

lim x 0 ( cos x ) 1 / 2 ( cos x ) 1 / 3 1 cos 2 x = lim x 0 ( cos x ) 1 / 2 ( cos x ) 1 / 3 ( 1 + cos x ) ( 1 cos x ) = ( lim x 0 1 1 + cos x ) ( lim x 0 ( cos x ) 1 / 2 ( cos x ) 1 / 3 1 cos x ) = 1 2 lim x 0 ( cos x ) 1 / 2 ( cos x ) 1 / 3 1 cos x \begin{aligned} \displaystyle \lim_{x \to 0} \dfrac{ {(\cos x)}^{1/2} - {(\cos x)}^{1/3} }{ 1 - \cos^2 x } &= \lim_{x \to 0} \dfrac{ {(\cos x)}^{1/2} - {(\cos x)}^{1/3} }{ (1+\cos x) (1-\cos x) } \\ &= \left( \lim_{x \to 0} \dfrac{1}{1+\cos x} \right) \cdot \left( \lim_{x \to 0} \dfrac{ {(\cos x)}^{1/2} - {(\cos x)}^{1/3} }{ 1 - \cos x } \right) \\ &= \dfrac 12 \cdot \lim_{x \to 0} \dfrac{ {(\cos x)}^{1/2} - {(\cos x)}^{1/3} }{ 1 - \cos x } \end{aligned}

Tapas Mazumdar - 4 years, 2 months ago

I think that should be 2x, But Didnt it affected the answer? I guess it was a Typo while he was coding.

Md Zuhair - 2 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...